Co-processamento de dregs em argila para produção de cerâmica vermelha - Fausto Rodrigues de Amorim (2007)
Co-processing is a technology widely applied in the cement industry. Potentially the structural ceramic industry also may absorb different industrial residues by incorporation in clay masses for fabrication of bricks and tiles. This work was accomplished in partnership with SuzanoCelulose e Papel Mucuri/BA and two red ceramic factories: Itabatan and Socopel. The purpose was to study the technical and environmental feasibility of co- processing dregs in clay for the manufacture of red bricks and roofing tiles. Test bodies were made in the measures of 15 x 25 x 75mm with 0, 5, 10, 15 and 20% of dregs in clay. After drying at 110°C and burning at 750, 850 and 950°C maintaining constant maximum temperature for 1 or 3h, the test bodies were submitted to physical mechanical and chemical assays. The test bodies with 20% of dregs in clay, when compared with bodies without dregs, showed 30% increase in dry flexural strength. Those burnt at 850°C, maintaining this temperature for one hour, increased the flexural strength and water absorption in 100 and 65%, respectively, when compared with bodies without dregs addition. Some elements were found in water extract in concentrations above the limit specified by Brazilian Norm NBR 10004. Despite this, thebricks made with 20% dregs and burning temperature of 850°C showed low risk to humane health and environment. It may be concluded that the co-processing of dregs in ceramic materials is of advantage to generating and co-processing companies.